Thinking outside the box—The associations with cutaneous involvement and autoantibody status in systemic sclerosis are not always what we expect - Srivastava, Neha; Hudson, Marie; Tatibouet, Solène; Wang, Mianbo; Baron, Murray; Fritzler, Marvin J. (Seminars in arthritis and rheumatism, 2015)
To describe the clinical characteristics and survival of anti-topoisomerase antibody positive (ATA+) limited cutaneous systemic sclerosis (lcSSc) and anti-centromere antibody positive (ACA+) diffuse cutaneous systemic sclerosis (dcSSc) patients in a large, multicenter SSc cohort. Data from subjects in the Canadian Scleroderma Research Group (CSRG) cohort were extracted. Descriptive statistics were used to summarize the baseline characteristics, including sociodemographic, clinical and serological features of lcSSc and dcSSc, according to ATA+ and ACA+ subsets. Kaplan–Meier analysis was performed to investigate survival by subsets. Of the 551 subjects included in this study, 52 (9.4%) had ATA+ lcSSc and 91 (16.5%) had ACA+ dcSSc. Demographic and visceral organ involvement (e.g., gastrointestinal symptoms, interstitial lung disease, pulmonary hypertension, and scleroderma renal crisis) was associated with serologic status more so than with skin subset. On the other hand, calcinosis, joint and peripheral vascular manifestations were associated with skin rather than antibody status. Survival was associated with both skin and autoantibody subsets, with ATA + dcSSc associated with the worse survival compared to ATA+ lcSSc (p = 0.0115), ACA+ lcSSc (p = 0.0216) and ACA+ dcSSc (p = 0.0313). This study provides evidence that subsetting using antibody markers in addition to extent of skin involvement may predict clinical outcomes better than skin or serology alone in SSc. These findings can inform ongoing efforts to define more robust SSc subsets compared to those based on the extent of skin involvement or serology alone.